Move The Object or Move The User: The Role of Interaction Techniques on Embodied Learning in VR - Bagher, Mahda M.; Sajjadi, Pejman; Wallgrün, Jan Oliver; La Femina, Peter C.; Klippel, Alexander (Frontiers in Virtual Reality, 2021)
To incorporate immersive technologies as part of the educational curriculum, this article is an endeavor to investigate the role of two affordances that are crucial in designing embodied interactive virtual learning environments (VLEs) to enhance students’ learning experience and performance: (1) the sense of presence as a subjective affordance of the VR system, and (2) bodily engagement as an embodied affordance and the associated sense of agency that is created through interaction techniques with three-dimensional learning objects. To investigate the impact of different design choices for interaction, and how they would affect the associated sense of agency, learning experience and performance, we designed two VLEs in the context of penetrative thinking in a critical 3D task in geosciences education: understanding the cross-sections of earthquakes’ depth and geometry in subduction zones around the world. Both VLEs were web-based desktop VR applications containing 3D data that participants ran remotely on their own computers and on a normal screen. In the drag & scroll condition, we facilitated bodily engagement with the 3D data through object manipulation, and in the first-person condition, we provided the ability for the user to move in space. In other words, we compared moving the objects or moving the user in space as the interaction modalities. We found that students had a better learning experience in the drag & scroll condition but we could not find a significant difference in the sense of presence between the two conditions. Regarding learning performance, in both conditions, we found a positive correlation between the sense of agency and knowledge gain. In terms of students with low prior knowledge of the field, exposure to the VR experience in both conditions significantly improved their knowledge gain. In the matter of individual differences, we investigated the knowledge gain of students with a low penetrative thinking ability. We found that they benefited from the type of bodily engagement in the first-person condition and had a significantly higher knowledge gain compared to the other condition. Our results encourage the continuation of in-depth studies of embodied learning in VR to design more effective embodied virtual learning environments.